2004
DOI: 10.3727/000000004783983891
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Stem Cells Form Articular Cartilage, not Teratomas, in Osteochondral Defects of Rat Joints

Abstract: Embryonic stem (ES) cells are considered to be a potential tool for repairing articular cartilage defects, but so far it has been impossible to cause these cells to differentiate into chondrocytes exclusively, either in vivo or in vitro. To explore a potential new cell source of cell transplantation for articular cartilage defects, we transplanted ES cells into articular cartilage defects in immunosuppressed rats. ES cells (AB2.2 or CCE cells) were transplanted into articular cartilage defects in the patellar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 20 publications
1
48
0
Order By: Relevance
“…ES and iPS cells do not face the problem of deterioration during cell passaging. Tanigami and collaborators had reported that they were successful in regenerating rat knee joint cartilage by transplanting undifferentiated mouse ES cells embedded in collagen gel into the knee joint defect model, and just by letting the rats freely mobilize their knees (25). This study suggested that undifferentiated ES cells could be differentiated and organized into proper tissues just by being placed in a physiological environment.…”
Section: Introductionmentioning
confidence: 82%
“…ES and iPS cells do not face the problem of deterioration during cell passaging. Tanigami and collaborators had reported that they were successful in regenerating rat knee joint cartilage by transplanting undifferentiated mouse ES cells embedded in collagen gel into the knee joint defect model, and just by letting the rats freely mobilize their knees (25). This study suggested that undifferentiated ES cells could be differentiated and organized into proper tissues just by being placed in a physiological environment.…”
Section: Introductionmentioning
confidence: 82%
“…Currently, much of the emphasis, which is backed by considerable investment, is being placed on the controlled differentiation of ESCs along given cell lineages, including cartilage and bone (21)(22)(23). However, in the case of cartilage repair, which is a key target for regenerative medicine, several cell-based repair strategies already exist, including implantation of cultureexpanded articular chondrocytes, implantation of culture-expanded MSCs, and bone microfracture techniques, among other strategies (14,24,25).…”
Section: Existing Msc-based Cartilage and Bone Therapiesmentioning
confidence: 99%
“…Wakitani et al [71] transplanted ESCs into articular cartilage defects in immunosuppressed rats, with the ESCs producing cartilage which resulted in repair of the defects at 8 weeks after the transplantation without formation of any teratomas. Hwang et al [72] treated rat osteochondral defects with chondrogenically committed human ESC derived MSCs.…”
Section: Embryonic Stem Cellsmentioning
confidence: 99%